Redes multicódigos: possibilidades semióticas para o ativismo global (Significação: Journal of Audiovisual Culture, 2004)
Research conceming possible relationships between hypermedia, as a tool for global direct political actions, and the formation of conduct habits connected to participatory democracy and a renewed internationalism. This involves an analysis about global demonstrations and events organízation and releasing, stressing multicode semiotic processes. In the end, action proposals based on the logician Charles Sanders Peirce's notion of genuine sign are launched.